2021
DOI: 10.15850/amj.v8n1.2097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Narcissism, Self-Esteem, and Social Media Addiction in Preclinical Medical Students

Abstract: Background: Narcissism is a condition in which people have a constant demand to be complimented and prioritized. Self-esteem is a subjective evaluation of one's worth. Several studies have linked narcissism and low self-esteem as a risk factor of social media addiction, a disorder where individuals displayed an unhealthy compulsion to access social media until it disrupts other activities. This study aimed to discover the relationship between narcissism, self-esteem, and social media addiction in preclinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Consistent with this result, prior studies also demonstrated that narcissism correlated with different kinds of addictive behaviors including Facebook addiction (Brailovskaia et al, 2020). Other research also revealed that narcissism was linked to social media addiction in adulthood (Susanto et al, 2021). For example, individuals displaying narcissistic traits use social media more often because it provides them the opportunity to share faultless pictures, videos, and words about themselves in a very controlled way which helps construct a fantasy identity (Mehdizadeh, 2010).…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with this result, prior studies also demonstrated that narcissism correlated with different kinds of addictive behaviors including Facebook addiction (Brailovskaia et al, 2020). Other research also revealed that narcissism was linked to social media addiction in adulthood (Susanto et al, 2021). For example, individuals displaying narcissistic traits use social media more often because it provides them the opportunity to share faultless pictures, videos, and words about themselves in a very controlled way which helps construct a fantasy identity (Mehdizadeh, 2010).…”
Section: Discussionmentioning
confidence: 53%